2015
DOI: 10.3126/kumj.v12i1.13625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Dose Intramuscular Methylprednisolone Injection into the Masseter Muscle on the Surgical Extraction of Impacted Lower Third Molars: a Randomized Controlled Trial

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The results of the same are listed in [Table/ Fig-1] [14][15][16][17][18][19][20][21][22][23][24]. Most of these studies have administered corticosteroids preoperatively whereas in our study we administered it postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the same are listed in [Table/ Fig-1] [14][15][16][17][18][19][20][21][22][23][24]. Most of these studies have administered corticosteroids preoperatively whereas in our study we administered it postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…As for the decision to perform pre-emptive administration, this was done solely based on the reports by several authors who showed that pre-emptive administration was significantly better than administration performed postoperatively. 7,[22][23][24][25] The rationale behind preemptive administration is that corticosteroids should be given before the onset of the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Different administration routes have been used for these drugs in oral surgery [10]. The use of oral forms might cause gastrointestinal upset, and steroids are best taken with food [11]. Effectiveness of the oral route of administration is dependent on patient compliance, and repeated dosing is required to maintain adequate blood levels during the postoperative period.…”
Section: Discussionmentioning
confidence: 99%